2012
DOI: 10.1111/j.1528-1167.2012.03508.x
|View full text |Cite
|
Sign up to set email alerts
|

Good interobserver and intraobserver agreement in the evaluation of the new ILAE classification of focal cortical dysplasias

Abstract: SUMMARYPurpose: An International League Against Epilepsy (ILAE) consensus classification system for focal cortical dysplasias (FCDs) has been published in 2011 specifying clinicopathologic FCD variants. The aim of the present work was to microscopically assess interobserver agreement and intraobserver reproducibility for FCD categories among an international group of neuropathologists with different levels of experience and access to epilepsy surgery tissue. Methods: Surgical FCD specimens covering a broad his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 15 publications
(20 reference statements)
0
42
0
5
Order By: Relevance
“…61,70 The new classification 12 attempts to elaborate a comprehensive view of the entire group of situations in which FCD can be encountered, whether alone or in association, and it has been shown to considerably improve the reproducibility of FCD diagnosis. 21 To our knowledge, our study is the first effort to assess the impact of this new classification on surgical practice and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61,70 The new classification 12 attempts to elaborate a comprehensive view of the entire group of situations in which FCD can be encountered, whether alone or in association, and it has been shown to considerably improve the reproducibility of FCD diagnosis. 21 To our knowledge, our study is the first effort to assess the impact of this new classification on surgical practice and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…14,16,86,98 In the setting of ELGT, the distinction among the various subtypes of tumors is essential for predicting the seizure outcome and the oncological behavior. In fact, gangliogliomas and dysembryoplastic neuroepithelial tumors may have pronounced intrinsic epileptogenic properties due to their neuronal and glial components, 14,21,23,[25][26][27] and their complete removal may lead to seizure freedom. With respect to oncological behavior, ELGTs are usually indolent WHO Grade I lesions, although several reports have demonstrated that gangliogliomas may potentially have an evolving course and may demonstrate malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the histopathologic classification of these patients was decided by a sole neuropathologist. Given the interobserver variability in applying both the ILAE and the Palmini et al classification systems, 13,18 it is possible that some cases would have been classified as a different subtype by another pathologist. Second, there was somewhat inconsistent specimen processing.…”
Section: Discussionmentioning
confidence: 99%
“…A task force of the Diagnostic Methods Commission of the International League Against Epilepsy (ILAE) has recently generated a new consensus classification of distinct FCD subtypes based on histopathological features [6]. A recent evaluation of this classification system showed good inter-and intra-observer agreement [99], with considerable improvement compared with a previous study evaluating the 2004 Palmini FCD classification [100]. This 2011 ILAE classification consists of a three-tiered system, including both isolated and associated FCD variants [6].…”
Section: Clinical and Neuropathologic Featuresmentioning
confidence: 99%